Characterization of the evolution of thermal maturity and pore structure of continental organic-rich shales - Li, Yanju; Wu, Yuandong; Zhao, Ruirui; Jiang, Shengling; Du, Xuanhong (Frontiers in Earth Science, 2024)
To clarify the evolution of thermal maturity and pore structure in continental organic-rich shales, calcareous shales of the Liaohe Basin (China) were pyrolyzed, and examined using Raman spectroscopy, Fourier transform infrared spectroscopy (FTIR), X-ray diffraction (XRD), X-ray photoelectron spectroscopy (XPS), scanning electron microscopy (SEM), nitrogen sorption isotherms, and nuclear magnetic resonance (NMR) spectroscopy. The increase in Raman G‒D band separation and decrease in Raman ID/IG ratio with increasing thermal maturity indicate that these parameters provide superior thermal maturity indicators. This is also confirmed by the good linear correlation of G‒D band shifts and ID/IG with vitrinite reflectance (VR) and maximum temperature (Tmax), respectively. The relative detection accuracy (DA), sampling requirements (SR), sample preparation (SP), detection time (DT), and equipment requirement (ER) of VR, G‒D band shifts, ID/IG, Tmax, FTIR, and XPS indicate that Raman analysis is a simple, quick, and robust method to evaluate thermal maturity. The moderate SR, complex SP, and long DT suggest that VR and Tmax are less widely applicable for characterizing thermal maturity. The FTIR and XPS techniques provide semi-quantitative maturity indicators with poor DA and high ER. Pores observed within organic matter and minerals under SEM indicate that an increase in thermal maturity not only affects the development of organic pores but is also beneficial for the formation of mineral dissolution pores, such as those formed during the transformation of Na0.95Ca0.16Al1.16Si2.84O8 to Na0.84Ca0.02Al1.02Si2.98O8, a process confirmed by XRD. The BET and NMR data also indicate that the development of pore structure is closely related to the evolution of thermal maturity in calcareous shale. During the initial stage, primary pores are filled by bitumen generated from kerogen; this leads to a decrease in transition pores, mesopores, and shale porosity, and reduced pore connectivity. Then, secondary nanoscale pores, transition pores, and mesopores increase with increasing thermal maturity. The peak in secondary porosity is consistent with the liquid hydrocarbon production rate peak, a process that increases shale porosity and leads to improved pore connectivity. The dissolution of minerals induced by organic acids may also contribute to this secondary porosity. With a further increase in thermal maturity, secondary porosity at the microscale is further developed, while transition pores and mesopores collapse, resulting in reduced pore connectivity. The poor pore connectivity that occurs at both low and high VR values may be more conducive to the preservation of shale oil and gas. This study is significant for research into the evolution of thermal maturity and pore structure in continental organic-rich shales.